Ratiometric fluorescence sensing of endogenous sulfur dioxide derivatives: Bio-imaging application in lipid droplets. (August 2021) - Yang, Di; Ning, Jun-Ya; Wu, Xiao-Tian; Yao, Wen; Shi, Hao-Nan; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: Two ratiometric fluorescence probes, RMC and RMD, were synthesized for detecting HSO3 − in test tube and living cells. Probe RMC based on FRET mechanism exhibited excellent ratiometric signals, high sensitivity (1.08 nM), outstanding selectivity, fast response (within 22 s) to HSO3 − in physiological pH. The satisfactory performance of RMC in cell imaging suggested that it could be applied to monitor endogenous and intracellular bisulfite with minimal cytotoxicity and excellent photostability. More importantly, probe RMC realized targeting for lipid droplets. In practice, probe RMC could be successfully applied to detect HSO3 − in food sugar. Besides, cheap test strips were made and used handily for rapid and qualitative detection of HSO3 − in water by naked eye as well. Therefore, probe RMC could be a potential biological tool to explore the roles of HSO3 − under different physiological and pathological conditions. Graphical abstract: Image 1 Highlights: Two ratiometric fluorescence probe RMC and RMD based on FRET for bisulfite were developed. Probe RMC could reveal a response in 22 s toward HSO3 − with high selectivity and sensitivity. Probe RMC could target lipid droplets in living cells. Probe RMC could detect HSO3 − in sugar solution. The test strips could be made handily for rapid and qualitative detection.